The Processing Characteristics of Canned Lemuru Fish (Sardinella lemuru) using Tomato Sauce Media - Handoko, Yudi Prasetyo; Thabrani, Muhamad Prayogi (PELAGICUS, 2022)
Lemuru fish have high economic value, and one of them is used as canned lemuru fish products. The purpose of this study was to determine the processing characteristics of canned lemuru fish including determine the flow of process, determine the quality of raw materials and final products, application of temperature, yield produced, employee productivity, application of GMP (Good Manufacturing Practices) and SSOP (Sanitation Standard Operating Procedure), and application of waste management system. The research method used is descriptive and comparative. Primary data retrieval is done by participating in the production process, observing and interviewing employees, while secondary data is obtained from company archives/documentation. The canned lemuru was made in 18 processing stages, from raw material receiving to shipping. The results of the organoleptic test of raw materials and sensory tests of the final product showed a value of 9. Microbiological tests on raw materials and products have complied with the national standards. Chemical tests of raw materials and final products obtained histamine levels of 3.125 ppm and 3.625 ppm. The temperature of lemuru during processing has met the temperature standards by the company. The yield of lemuru at the pre-cooking stage was 83.95 ± 0.02%, and at the cutting stage it was 63.64 ± 0.01%. Productivity at the cutting stage reached 37.84 ± 1.07 kg/hour/person and 45.16 ± 5.60 kg/hour/person at the filling stage. Sanitation and Hygiene has been carried out well as evidenced by the existence of SSOP, GMP, and processing feasibility certificates. Solid waste in the form of coal waste, aval waste namely fish heads, tails, and entrails are processed into fish meal. The resulting liquid waste is processed in the IPAL (Instalasi Pengolahan Air Limbah).